The effect of ancient totemic beliefs on the Kazakh traditional singing - A. S., Sabirova; Issametova K. I., Mukanova A. B.,; M. E., Sultanova; A. T., Yergalieva (Opción, 2020)
The Kazakh musical culture has undoubtedly a rich history that stretches back to ancient time. The philosophy of the Kazakh people is laced with mythological beliefs, with belief in higher forces, magic. Music has always had a sacral meaning for the Kazakhs; all the major life stages were accompanied with the corresponding folk songs. Totemic beliefs occupy a special place in the philosophy of the Kazakh music. This article seeks to establish the relationship between totemic in the Kazakh culture and traditional singing. The evolution of totemic symbols and their role in the life of Kazakh people were observed.